Interpretation of deep seismic reflection profiles in the northern part of the Malé Karpaty Mountains - KYTKOVÁ, Bibiána; TOMEK, Čestmír; BIELIK, Miroslav; PUTIŠ, Marián (Contributions to Geophysics and Geodesy, 2021)
We present in this paper some results of the interpretation of deep seismic reflection profiling across the northern part of the Malé Karpaty Mountains. The goal was to recognize the tectonic character of western and eastern mountain range limitation in the area between Plavecký Mikuláš and Dolné Orešany, study the character of the Záhorský fault and the declination of inner structures. The result of the interpretation was the confirmation that the Vienna Basin is a pull-apart basin and that the western mountain range border is formed by an orthogonal strike slip connected with the mountain range uplift. On the eastern border (from the Danube Basin side) what was until now considered as fault, appears to be a fold. Hence, the Malé Karpaty Mountains represent at least in the northern part an anticline.